Conservation of social effects (Ψ) between two species of Drosophila despite reversal of sexual dimorphism. Issue 23 (22nd October 2017) - Signor, Sarah A.; Abbasi, Mohammad; Marjoram, Paul; Nuzhdin, Sergey V.
Abstract: Indirect genetic effects (IGEs) describe the effect of the genes of social partners on the phenotype of a focal individual. Here, we measure indirect genetic effects using the "coefficient of interaction" (Ψ) to test whether Ψ evolved between Drosophila melanogaster and D. simulans . We compare Ψ for locomotion between ethanol and nonethanol environments in both species, but only D. melanogaster utilizes ethanol ecologically. We find that while sexual dimorphism for locomotion has been reversed in D. simulans, there has been no evolution of social effects between these two species. What did evolve was the interaction between genotype‐specific Ψ and the environment, as D. melanogaster  varies unpredictably between environments and D. simulans  does not. In this system, this suggests evolutionary lability of sexual dimorphism but a conservation of social effects, which brings forth interesting questions about the role of the social environment in sexual selection. Abstract : We measure indirect genetic effects using the 'coefficient of interaction' (Ψ) to test whether Ψ evolved between Drosophila melanogaster and D. simulans . We compare Ψ for locomotion between ethanol and non‐ethanol environments, which only D. melanogaster utilizes ecologically. We find that while sexual dimorphism has been reversed in D. simulans, there has been no evolution of social effects between these two species.